Запасні білки як універсальний маркер ідентифікації генотипів сільськогосподарських рослин - Сірант, Л.В.; Дикун, М.О.; Завальна, Г.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. Identify electrophoretic spectras of polymorphism hordeyin, zein and helianthin. Methods. Methods electrophoretic
separation of storage proteins in poliakrilamid gel. Results. Identified barley varieties and typicality hybrids of sunflower
and maize. Selected for each crop of storage proteins electrophoresis techniques and optimized some parts of this
techniques. Performed for differentiation barley varieties with similar spectra albumin’s electrophoresis. Foreign malting
barley varieties are higher than domestic varieties. Conclusions. In general, the method of electrophoresis is able to
provide good results and can be used for mass analysis.
Keywords: electrophoresis, hordein, heliantinin, zein.